Foucaldienne, la psychanalyse ? - Pascale Molinier (Genre, Sexualité et Société)
"Psychoanalysis will be Foucauldian, or will not be". Jean Allouch, the author of this maxim, returns to the importance of Michel Foucault in his own career as a psychoanalyst, student of Lacan, author of psychoanalytical essays and director of the collection Les Grands classiques de l'érotologie moderne (Great Classics of Modern Erotology). Psychoanalysis will be Foucauldian if, continuing Freud's inaugural movement, it persists in defending itself from a medical or positivist position, and if it is critically confronted with the current knowledge, in particular gay and lesbian studies.